2011
DOI: 10.1016/j.apm.2010.11.021
|View full text |Cite
|
Sign up to set email alerts
|

On the discrete-time Geo/G/1 queue with randomized vacations and at most J vacations

Abstract: a b s t r a c tThis paper examines a discrete-time Geo/G/1 queue, where the server may take at most J À 1 vacations after the essential vacation. In this system, messages arrive according to Bernoulli process and receive corresponding service immediately if the server is available upon arrival. When the server is busy or on vacation, arriving messages have to wait in the queue. After the messages in the queue are served exhaustively, the server leaves for the essential vacation. At the end of essential vacatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Such a modified vacation discipline has potentially applications in practical systems [13], for example, in some stochastic production and inventory control systems such as production to orders. This is a continuation of work by Wang et al(2011) [16] and Luo et al (2013) [17] where they study the queue size distribution for / /1 with randomized vacation and at most vacations by using different methods, respectively. Instead of studying the queue size distribution studied in [16,17], this paper considers another theme-the departure process in that discrete-time model.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Such a modified vacation discipline has potentially applications in practical systems [13], for example, in some stochastic production and inventory control systems such as production to orders. This is a continuation of work by Wang et al(2011) [16] and Luo et al (2013) [17] where they study the queue size distribution for / /1 with randomized vacation and at most vacations by using different methods, respectively. Instead of studying the queue size distribution studied in [16,17], this paper considers another theme-the departure process in that discrete-time model.…”
Section: Introductionmentioning
confidence: 60%
“…This is a continuation of work by Wang et al(2011) [16] and Luo et al (2013) [17] where they study the queue size distribution for / /1 with randomized vacation and at most vacations by using different methods, respectively. Instead of studying the queue size distribution studied in [16,17], this paper considers another theme-the departure process in that discrete-time model. The investigation of departure process in a queueing system is primarily motivated by the need to analyze queueing network models, in which the departure process of an upstream queue is the arrival process of the downstream queue.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Over the past decades, Geo/G/1 queues and Geo/G/1 retrial queues with a variety of vacation policies have been well developed, such as Takagi [2], Zhang and Tian [16], Gao and Wang [17], Wang [18], Wang et al [19], Yue and Zhang [20], Luo et al [21], and Wang [22,23] (not exhaustive list). However, most of these vacation queues deal with the case of single waiting queues; i.e., there is only a waiting queue in the service area in the Geo/G/1 queue or an orbit waiting queue in the Geo/G/1 retrial queue.…”
Section: Related Workmentioning
confidence: 99%
“…A comprehensive review of vacation queues can be found in the surveys of Doshi [5] and Ke et al [12], and the monographs of Takagi [24] and Tian and Zhang [25]. In the recent past, remarkable contributions on discrete-time queueing systems with vacations have been made by many authors (see e.g., Zhang and Tian [32], Tang et al [23], Wang et al [27], Wang [28], Goswami and Mund [10], Laxmi and Jyothsna [20], and Gao and Wang [11]).…”
Section: Introductionmentioning
confidence: 99%